The dumbest generation : how the digital age stupefies young Americans and jeopardizes our future - Bauerlein, Mark. (New York : Jeremy P.Tarcher/Penguin, 2009)
The technology that was supposed to make young adults more astute, diversify their tastes, and improve their minds had the opposite effect. According to recent reports from government agencies, foundations, survey firms, and scholarly institutions, most young people in the United States do not read literature (or fully know how to), work reliably (just ask employers), visit cultural institutions (of any sort), or vote (most can't even understand a simple ballot). They cannot explain basic scientific methods, recount fundamental facts of American history, or name any of their local political representatives. What they do happen to excel at is - each other. They spend unbelievable amounts of time electronically exchanging stories, pictures, tunes, and texts, savoring the thrill of peer attention and dwelling in a world of puerile banter and coarse images." "Drawing upon exhaustive research, detailed portraits, and historical and social analysis, The Dumbest Generation presents an uncompromisingly realistic study of the young American mind at this critical juncture. The book also lays out a compelling vision of how we might address its deficiencies."--Jacket.
Includes bibliographical references and index.
Keywords: Young adults -- Effect of technological innovations on -- United States; Technology and youth -- United States; Young adults -- Attitudes. -- United States; Internet -- Social aspects -- United States